The Effect of Condensation on the Morphology and Magnetic Properties of Modified Barium Hexaferrite (BaFe12O19) - Durmus, Z.; Sozeri, H.; Toprak, M. S.; Baykal, A. (Nano-Micro Letters, 2011)
We present a comparison for the effect of condensation on the morphology and magnetic properties of oleic acid modified BaFe12O19 nanoparticles. Two different samples of BaFe12O19 nanoparticles were synthesized by dehydration (Z1) and rotary evaporation (Z2) method, respectively. Oleic acid was used as the surface modification agent to observe the morphological and magnetic changes. The nanoparticles were analyzed by XRD, FTIR, TGA, SEM, and VSM techniques for structural and physicochemical characteristics. Crystallographic analysis reveals the phase as hexaferrite and the average crystallite size of Z1 and Z2 is 21±3 nm and 17±2 nm, respectively. Rotary evaporator accelerates the condensation process in viscous gel (Z2). Due to the use of rotary evaporator, the coating with oleic acid for Z2 product has been accomplished very well, as compared with Z1. As a result, saturation magnetization of Z2 sample is much lower than that of Z1 sample.